How September 11 changed American foreign policy: The record a year later - Peter Rudolf (Stiftung Wissenschaft und Politik (SWP), 2002)
September 11 presented the Bush administration with the opportunity for a strategic reorientation of American foreign policy. Contrary to the hopes of many, however, this chance was not used to move towards a more multilateral policy, rather it was used to mobilize resources to the benefit of a superpower policy with a strong emphasis on military might. In light of increased perception of asymmetrical threats and with the "War on Terrorism" as legitimizing principle, those who advocate a policy based on superior military power and unrestricted room to maneuver have succeeded in dominating the foreign policy discourse in the US. The more such thinking determines the policy of the Bush administration - and in many areas it has already shaped decisions - the more this will lead to strategic divergence between the US and Europe.(SWP Comments / SWP)
Keywords: 320